How to tackle mental fatigue: a systematic review of potential countermeasures and their underlying mechanisms - Proost, M.; Habay, J.; De Wachter, J.; De Pauw, K.; Rattray B.; Meeusen, R.; Roelands, B.; Van Cutsem, J. (Sports Medicine, 2022)
Introduction: Mental fatigue (MF) is a psychobiological state that impairs cognitive as well as physical performance in different settings. Recently, numerous studies have sought ways to counteract these negative effects of MF. An overview of the explored countermeasures for MF is, however, lacking. Objectives: The objective of this review is to provide an overview of the different MF countermeasures currently explored in literature. Countermeasures were classified by the timing of application (before, during or after the moment of MF) and type of intervention (behavioural, physiological and psychological). Methods: The databases of PubMed (MEDLINE), Web of Science and PsycINFO were searched until March 7, 2022. Studies were eligible when MF was induced using a task with a duration of at least 30 min, when they assessed MF markers in at least two out of the three areas wherein MF markers have been defined (i.e., behavioural, subjective and/or [neuro]physiological) and used a placebo or control group for the countermeasure. Results: A total of 33 studies investigated one or more countermeasures against MF. Of these, eight studies assessed a behavioural countermeasure, 22 a physiological one, one a psychological countermeasure and two a combination of a behavioural and psychological countermeasure. The general finding was that a vast majority of the countermeasures induced a positive effect on behavioural (e.g., task or sport performance) and/or subjective MF markers (e.g., visual analogue scale for MF or alertness). No definitive conclusion could be drawn regarding the effect of the employed countermeasures on (neuro)physiological markers of MF as only 19 of the included studies investigated these measures, and within these a large heterogeneity in the evaluated (neuro)physiological markers was present. Discussion: Within the physiological countermeasures it seems that the use of odours during a MF task or caffeine before the MF task are the most promising interventions in combating MF. Promising behavioural (e.g., listening to music) and psychological (e.g., extrinsic motivation) countermeasures of MF have also been reported. The most assumed mechanism through which these countermeasures operate is the dopaminergic system. However, this mechanism remains speculative as (neuro)physiological markers of MF have been scarcely evaluated to date. Conclusion: The present systematic review reveals that a wide range of countermeasures have been found to successfully counteract MF on a subjective, (neuro)physiological and/or behavioural level. Of these, caffeine, odours, music and extrinsic motivation are the most evidenced for countering MF. To provide in-detail practical guidelines for the real-life application of MF countermeasures, more research must be performed into the underlying mechanisms and into the optimal dosage and time of application/intake.